Honey, I'll be working late tonight. The effect of individual work routines on leisure time synchronization of couples - Juliane Scheffel (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
German time use data for 2001/02 are used to assess the impact of workplace characteristics on the private life of couples. The major aim is to solve the endogeneity resulting from individual preferences for work and leisure to identify the pure effects of the workplace independent from other diluting personal influences in a cross-sectional setting when no appropriate instruments are available. I propose a repeated random assignment of people into pseudo couples as a solution. By this approach, I am able to uncover additional marriage inherent mechanisms that result in a (de-)synchronization of joint time that are still family friendly.
Keywords: D13; J12; J16; J22; 330; Time Use; Time Allocation; Family Economics; Flexibility; Synchronization; Leisure; Endogeneity; Zeitbudgetforschung; Familienökonomik; Arbeitsplatz; Arbeitszeit; Freizeit; Zeitallokation; Schätzung; Deutschland